'The Blair that I know is a toilet': political nicknames and hegemonic control in post-2000 Zimbabwe. Issue 2 (3rd April 2017) - Nyambi, Oliver
Abstract: Most studies on the political power conundrum in post-2000 Zimbabwe have concentrated more on overt and oftentimes contested manifestations of the ruling Zimbabwe African National Union Patriotic Front (ZANU PF) party's power retention strategies such as violence, intimidation and electoral fraud. The role of language and other subtle forms of political campaign and hegemonic sustenance such as nicknaming is still a grey area. This article argues that both within and outside ZANU PF, nicknaming in the post-2000 period has become more pronounced and along with more trusted forms of political campaign, has been consciously deployed by the ruling party to shore up its electability. A critical analysis of focal nicknames and nicknaming patterns in ZANU PF discourses reflects an overarching attempt to manipulate language to psychologically influence the electorate to emotionally perceive the conveniences of electing the party and the liabilities attendant on choosing its opponents.